Efficacy of Cognitive Behavioral Group Therapy (CBGT) among children with anxiety disorders - Nilgun Ongider-Gregory; Burak Baykara (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: It was aimed to investigate efficacy of Cognitive behavioral group therapy (CBGT) in childhood anxiety disorders by pre and post therapy. Method: Trial sample was obtained from an university outpatient child psychiatry clinic. Therapy group (n=12) was selected from children and their parents whom was diagnosed as DSM-IV childhood anxiety disorder. And comparation group (n=12) was selected from children and their parents whom was in the waiting list. The total sample includes 72 indivudual. Before and after CBGT; sociodemographic data questionnaire and State-Trait Anxiety Inventory for Children was applied to children, State-Trait Anxiety Inventory was applied to parents. Results: Data analysis was done by Wilcoxon non-parametric test. Children whom in therapy group both state and trait anxiety levels was significantly reduced after CBGT sessions (z=-2.549 p<.01; z=-2.828 p<.001). There were significant differences between children of therapy group and the comparation group in wich state and trait anxiety levels . For parents from therapy group, state and trait anxiety levels was significantly reduced after CBGT sessions which were applied to their offsprings. Also there were significant differences between parents of therapy group and the comparation group both state and trait anxiety levels . Conclusion: Anxiety levels were reduced significantly after CBGT sessions and also differences between therapy and the comparation groups were important. Therefore it was interpreted that CBGT was effective for reducing anxiety levels in children. Anxiety levels of parents were reduced after their children’s CBGT sessions; it is showed that whole family is playing an important role in anxiety treatment. Many research in the literature highlights that parents play crucial role in emerging anxiety sympoms of their children. [JCBPR 2015; 4(1.000): 26-37]